Pollen record of the mid- to late-Holocene centennial climate change on the East coast of South Korea and its influential factors. (January 2018) - Song, Bing; Yi, Sangheon; Jia, Hongjuan; Nahm, Wook-Hyun; Kim, Jin-Cheul; Lim, Jaesoo; Lee, Jin-Young; Sha, Longbin; Mao, Limi; Yang, Zhongyong; Nakanishi, Toshimichi; Hong, Wan; et al.
Graphical abstract: Highlights: There is a centennial resolution climate record from 6842 cal yr BP to present. The general cooling trend was probably triggered by decreasing solar insolation. The precipitation was co-determined by westerlies and the East Asian Summer Monsoon. The ENSO activity may be an important factor for East Asian Summer Monsoon change. Abstract: To understand historical climate change in western Pacific coastal areas, a sediment core (SOJ-2) from the stable sedimentary environment of the Songjiho Lagoon on the east coast of South Korea was obtained for centennial-resolution palynological analysis. The ages of the SOJ-2 core is well controlled by carbon 14 dating with high-resolution accelerator mass spectrometry (AMS), and the results indicated a general warm to cold climate trend from the mid-Holocene to the present, which can be divided into two different stages: a warmer stage between 6842 and 1297 cal yr BP and a colder stage from 1297 cal yr BP to the present, with fluctuations during these stages. The climate was wetter from 6842 to 6227 cal yr BP and 4520 to 1297 cal yr BP and was drier from 6227 to 4520 cal yr BP. The climate changed to cold and dry during the period from 1297–425 cal yr BP. The impact of human activity on the climate began at approximately 1297 cal yr BP and became pronounced starting in 425 cal yr BP. The general cooling trend may represent a response to decreasing solar insolation; however, the relative dryness or wetness of the climate may have been co-determined by westerlies and the East Asian summer monsoon (EASM). The climate had a teleconnection with the North Atlantic region, resulting from changes in solar activity. Nevertheless, EI Niño–Southern Oscillation (ENSO) activity played an important role in impacting the EASM changes in western Pacific coastal areas.